Towards gender equality in social protection: Evidence gaps and priority research questions - Peterman, Amber; Kumar, Neha; Pereira, Audrey; Gilligan, Daniel O. (2020)
Despite high-level commitments made by global stakeholders to advancing gender equity and equality through social protection, and the important role of this shared objective, there remains significant evidence gaps in understanding what this means in practice. We have proposed five priority evidence gaps to advance this understanding, related to: 1) programme design, 2) regional knowledge, 3) measurement and analysis, 4) cost effectiveness, and 5) future-looking issues. These priorities do not operate in isolation; each interacts with and should be considered alongside the others. We acknowledge that they are not exhaustive and are influenced by the type of research and viewpoints we bring to the intersection of social protection and gender. For example, understanding long-term, lifecycle, and intergenerational effects are certainly of importance, despite not being included as a top priority here. In many ways, setting out a research agenda for leveraging social protection for gender equality is similar to one which simply aims to make systems and programmes work better overall—no programme can fulfill objectives of poverty, inequality, and vulnerability while leaving half the population behind. We look forward to helping close these gaps.